Optimal Design of Rectangular Tank Walls With Ribs Using Numerical Models and Global Optimization - Garbowski, Tomasz; Borecki, Przemysław; Rutkowski, Janusz; Szymczak-Graczyk, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper addresses the optimization of the cross-section in rectangular above-ground tank walls, incorporating vertical ribs and an optional top ring. The objective is to minimize the volume of concrete used, while maintaining key performance criteria such as keeping the maximum tensile stress below the material`s allowable limit and minimizing deflections. The analysis is performed using the finite element method (FEM), with the optimization handled through a local gradient-based algorithm (trust region method), supported by a multistart technique to navigate the complexity of the design space and avoid suboptimal solutions.
Keywords: rectangular concrete tanks with ribs; cross-section optimization; finite element method; trust region algorithm; multistart optimization